Analisis Kepuasan Pelanggan pada E-Commerce - Yafianus Garamba; Aryanto Nur (GLOBAL SCIENTS PUBLISHER, 2024)
This research aims to analyze customer satisfaction levels in e-commerce services and the factors influencing them. In the digital era, e-commerce has become a primary platform for consumers to conduct transactions, making a thorough understanding of customer satisfaction crucial for business sustainability. This study employs a survey method, distributing questionnaires to users of e-commerce platforms in Indonesia.The collected data were analyzed using descriptive analysis and linear regression to identify the relationship between variables such as product quality, delivery speed, customer service, and platform usability on customer satisfaction.The results show that product quality and delivery speed significantly affect customer satisfaction. In addition, ease of navigation and platform usability also positively contribute to user satisfaction. Meanwhile, responsive customer service, although important, has a lower impact compared to other factors. This research provides important implications for e-commerce managers to improve service quality and increase customer satisfaction, particularly in terms of delivery speed and the quality of products offered.In conclusion, e-commerce companies must continuously enhance the service aspects that most influence customer satisfaction to maintain competitiveness in an increasingly competitive market. This study also suggests that future research should consider other variables, such as customer loyalty and price perception, to provide a more comprehensive understanding.